Editorial (2020)
In thoughts with Borges, is an invitation to this issue of La Palabra journal to ponder the influence of this author within philosophy, literature, and culture. This time, Daniel Balderston has accepted our invitation to contribute to this issue in relation to his book How Borges Wrote – coming soon in Spanish; his paper published here is linked with the same research that is found this book. It is a genetic study of the manuscript of the rewritten The Garden of Forking Paths [El jardín de los senderos que se bifurcan] in Credit pages from an accounting ledger. The second draft of “Examination of the Work of Herbert Quain” [“Examen de la obra de Herbert Quain”] is deeply analyzed.  As a result of this study, Daniel states that it is possible to specify the date of this manuscript.